2020
DOI: 10.1038/s41598-020-75140-3
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer potential of persimmon (Diospyros kaki) leaves via the PDGFR-Rac-JNK pathway

Abstract: Persimmon leaves are known to have some beneficial effects, including ROS elimination, lipid circulation, and neuronal protection. However, their anti-cancer properties and the underlying mechanisms remain unclear. Herein, we show that treatment with the ethanol extract of persimmon, Diospyros kaki, leaves (EEDK) induces cancer cell death and inhibits cell proliferation. Using fluorescence resonance energy transfer (FRET) technology with genetically-encoded biosensors, we first found that EEDK stimulates a PDG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 79 publications
(83 reference statements)
1
8
0
Order By: Relevance
“…In addition, the presence of considerable amount of protein in the plant may be considered an avenue for building a complex compound with them embedded functional phytochemicals, some of which are thought to stop carcinogenesis through their antioxidant properties by interfering with oxidative stress signalling pathway and suppressing DNA damage. This is also in agreement with Kim et al [ 31 ] where it was pointed out that a member of Diospyros genus ( Diospyros kaki ) exhibited cell death via activation of platelet-derived growth factor receptors (PDGFRs) which serve as the active binding site for membrane auto-phosphorylation. Our experimental findings support the notion that the incorporation of D. villosa protein into supplements may play a role in cancer inhibition and retrogression.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the presence of considerable amount of protein in the plant may be considered an avenue for building a complex compound with them embedded functional phytochemicals, some of which are thought to stop carcinogenesis through their antioxidant properties by interfering with oxidative stress signalling pathway and suppressing DNA damage. This is also in agreement with Kim et al [ 31 ] where it was pointed out that a member of Diospyros genus ( Diospyros kaki ) exhibited cell death via activation of platelet-derived growth factor receptors (PDGFRs) which serve as the active binding site for membrane auto-phosphorylation. Our experimental findings support the notion that the incorporation of D. villosa protein into supplements may play a role in cancer inhibition and retrogression.…”
Section: Discussionsupporting
confidence: 92%
“…Persimmon leaves were reported to inhibit ROS elimination and cell proliferation. For example, ethanolic extract of PL, mainly containing flavonoids, was found to stimulate a platelet-derived growth factor receptor (PDGFR)-Ras-related C3 botulinum toxin substrate (Rac) signaling cascade in live cells [ 70 ]. They also found that downstream of the PDGFR-Rac pathway, where c-Jun N-terminal kinase (JNK) is activated by this extract.…”
Section: Pharmacological Effects Of Plmentioning
confidence: 99%
“…This effect was achieved by the higher expression of the sirtuin1/SIRT1 gene; a silent regulator of the apoptosis‐induced DNA damage (Rauf, Uddin, Patel, et al, 2017). (Kim et al, 2020; Kim et al, 2020; Kim, Shin, Seo, Noh, & Roh, 2020) correlated this antioxidant property to persimmon fruits active ingredients “polyphenolics, tannins, and ascorbic acid” through the use of ultraviolet, fluorescence, and infrared spectrophotometry. The antioxidant capacities of active ingredients were correlated to their binding abilities during their interaction with serum albumin (Kim, Park, et al, 2020).…”
Section: Pharmacological Actions Of Dsmentioning
confidence: 99%
“…A recent study confirmed that the ethanol extract of persimmon leaves demonstrated an ameliorative effect on hepatocellular carcinoma with poor prognosis via repressing HGF/Met signaling pathway (Ko et al, 2020). Another ancillary study reported that the same extract triggered PDGFR‐Rac‐JNK signaling axis, inducing cancer cell death (Kim, Suh, et al, 2020).…”
Section: Pharmacological Actions Of Dsmentioning
confidence: 99%